Business networks in halal food industries in Malaysia - Nor Aini Haji Idris, (Penerbit Universiti Kebangsaan Malaysia, 2013)
The processed halal food industry has been identified as a potentially economically important export industry in Malaysia, but the production of a final product is still at the infant stage compared to developed countries. A business network is one of the aspects that firms need to focus upon to ensure such a product can be successfully marketed. Utilizing 220 samples of halal firms from Peninsular Malaysia, the present study analyses the role of networking in expanding export of halal products at the global market. The discussion of the present paper focuses upon the effectiveness of firms’ competitiveness, especially in relation to business networks which was based upon the strategic alliances concept. The underlying logic of alliance formation is premised upon strategic needs and opportunities. When engaging in strategic alliances, firms combine their assets and capabilities in a cooperative policy to achieve competitive advantages. Several factors are identified that affect success when building entrepreneur networks, such as trust, commitment, selection choices, information technology, intermediary support, and the conduciveness of the external environment. The study finds that halal food firms in Malaysia are still weak in forming business networks, especially marketing networks, in order to penetrate the global market. This is due to problems faced by entrepreneurs, including the lack of trustworthiness and commitment; the lack of information technology; socialization problems; the failure to identify or select of business networks; and the role of agencies, such as institutions and the governmental sector. In order to fulfill the ambition of the Malaysian government to emerge as the regional halal hub, the present research suggests policies to increase firm’s competitiveness through the establishment of effective business networks.